(untitled) (Vietnam Journal of Community Medicine, 2024)
Objective: Determining the success rate and complication rate of laparoscopic Hartmann reversal. Subject and method: Retrospective study, descriptive analysis, patients undergoing laparoscopic surgery to restore intestinal circulation after Hartmann surgery at Thong Nhat Hospital, Ho Chi Minh City from February 2017 to September 2020. Results: The success rate of laparoscopic Hartmann reversal was 85.71%. The complication rate was 6.67%. Most complications are infection of the incision site where the old colostomy is located, there is only one case of anastomosis that has to be reoperated. Conclusion: Laparoscopic Hartmann reversal surgery is feasible, has a high success rate and low complication rate..